EBSD measurements of phlogopite glass ceramics - Wisniewski, Wolfgang; Rüssel, Christian (CrystEngComm, 2015)
Electron backscatter diffraction (EBSD) is applied to conventional glass ceramics containing fluorophlogopite. EBSD analysis is possible in crystals containing a relatively low defect density, while indexable EBSD patterns could not be obtained from curved phlogopite crystals. The glass ceramics are sensitive to the electron beam and subject to EBSD pattern degradation if the energy load is too high. The twinning relationship previously described for the defective core of the yo-yo-shaped crystals also occurs in the outer plates but with a much lower frequency. The [001] direction, however, is constant within the crystals. Conventional fluorophlogopite glass ceramics are analyzed by EBSD. A twinning relationship is observed throughout the entire microstructure.